Implementasi Sistem Pemadam Kebakaran Pada Ruang Tertutup Berbasis Arduino Menggunakan Logika Fuzzy - Rahmat Naharu Yanuar; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Fires occur not knowing the place and time, can occur anywhere and anytime. Some causes of fires are human error, electrical short circuit, cigarettes, stove etc. Related to many parties who replace losses with property, business entities, and casualties. Based on these problems, we need a system that can overcome fire problems and take preventive measures such as blackouts. In previous studies it could only be called monitoring in information or it could be called monitoring. In this study the parameters used are the DHT11 temperature sensor, the sensor as soon as possible MQ-2 and the on sensor. The output of the system is an action consisting of an actuator with an exhaust fan for immediate transfer and water pump for fire suppression. The Fuzzy Mamdani method is applied to the system to connect the determinant of fan and pump actuators as needed. There are 3 input variables used, namely temperature with 3 membership functions, as soon as possible with 3 membership functions, and fire with 4 membership functions and 2 output variables, namely exhaust fan with 4 membership functions and water pump with 4 membership functions. Must get 36 fuzzy rules. From the test results, the system can determine various conditions of the room with accuracy reaching 100%. In fuzzy testing, the percentage of success is 100%. This shows that the results of the fuzzy testing method on the system are in accordance with the design that has been made. The system output determines the output that is an actuator, which is fan speed and pump duration varies.